PEMBELAJARAN SASTRA ANAK BERBASIS BUKU CERITA BERGAMBAR:STUDI TINDAKAN PENINGKATAN LITERASI DI PKBM SURYA MUDA - Misna (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
This study aims to investigate and describe the use of picture storybooks in children’s literature education, as well as their effectiveness in enhancing reading interest and comprehension of story content among students on the Package A programme at the Surya Muda Community Learning Centre. The research method employed was Classroom Action Research (CAR), conducted cyclically over two cycles, with each cycle comprising the planning, implementation, observation, and reflection stages. Data collection was carried out comprehensively through passive participatory observation, cognitive tests, reading interest questionnaires, and documentation. The results of the study showed a significant improvement in literacy from the pre-action condition to Cycle I and Cycle II. In the pre-action stage, the students’ reading interest and comprehension were in the low category due to the dominance of monotonous conventional learning methods. Following the implementation of picture storybooks in Cycle I, interest and engagement in learning began to rise, although cognitive comprehension levels remained in the moderate category. In Cycle II, through the reinforcement of an interactive approach (directly observing pictures, retelling the story in their own words, and small-group discussions), pupils’ reading interest increased dramatically to reach the high category; their ability to understand the intrinsic elements of the story (characters, plot, setting, moral) was categorised as good; and the classroom became much more lively. The conclusion of this study is that children’s literature learning based on picture storybooks has been empirically proven to effectively enhance reading interest, reading comprehension skills, and to create an interactive and enjoyable classroom atmosphere of equality.